Colorectal cancer screening program using FIT: quality of colonoscopy varies according to hospital type - Portillo, Isabel; Idigoras, Isabel; Bilbao, Isabel; Arana-Arri, Eunate; Fernández-Landa, María José; Hurtado, Jose Luis; Sarasaqueta, Cristina; Bujanda, Luis; for the EUSKOLON study investigators (Endoscopy International Open, 2018)
Background and study aims To compare the quality of colonoscopy in a population-based coordinated program of colorectal cancer screening according to type of hospital (academic or non-academic).Patients and methods Consecutive patients undergoing colonoscopy after positive FIT (≥ 20 ug Hb/g feces) between January 2009 and September 2016 were prospectively included at five academic and seven non-academic public hospitals. Screening colonoscopy quality indicators considered were adenoma detection rate, cecal intubation rate, complications and bowel preparation quality. Results A total of 48,759 patients underwent colonoscopy, 34,616 (80 %) in academic hospitals and 14,143 in non-academic hospitals. Among these cases, 19,942 (37.1 %) advanced adenomas and 2,607 (5.3 %) colorectal cancers (CRCs) were detected, representing a total of 22,549 (46.2 %) cases of advanced neoplasia. The adenoma detection rate was 64 %, 63.1 % in academic hospitals and 66.4 % in non-academic hospitals (P < 0.001). Rates of advanced adenoma detection, cecal intubation and adequate colonic preparation were 45.8 %, 96.2 % and 88.3 %, respectively, and in all cases were lower (implying worse quality care) in academic hospitals (45.3 % vs 48.7 %; odds ratio [OR] 0.87, 95 % confidence interval [CI] 0.84 – 0.91; 95.9 % vs 97 %; OR 0.48, 95 % CI 0.38 – 0.69; and 86.4 % vs 93 %; OR 0.48, 95 % CI 0.45 – 0.5; respectively; P < 0.001 in all cases). In 13 patients, all in the academic hospital group, CRC was diagnosed after colonoscopy (0.26 cases × 1000 colonoscopies). Rates of CRC treated by endoscopy were similar in both types of hospital (30 %). The rate of severe complication was 1.2 % (602 patients), with no significant differences by hospital type: bleeding occurred in 1/147 colonoscopies and perforation in 1/329. One patient died within 30 days after screening colonoscopy. Conclusions The quality of colonoscopy was better in non-academic hospitals. The rate of detection of advanced neoplasia was higher in non-academic hospitals and correlated with the rate of post-colonoscopy CRC.